AB0711 EBV serological reactivation profile in primary sjÖgren's syndrome: A possible trigger of the active articular involvement?. (23rd January 2014) - Pasoto, S.G.; Natalino, R.R.; Chakkour, H.P.; Viana, V.S.; Bueno, C.; Leon, E.P.; Vendramini, M.B.; Levy Neto, M.; Bonfa, E.
Abstract : Background: Support: FAPESP #2010/10013-4, 2010/10017-0 and 2010/13463-0 Antibody to Epstein-Barr virus (EBV) early antigen diffuse (anti-EA-D) is associated with viral replication. However, their possible associations with clinical/therapeutic features in primary Sjögren's syndrome (pSS) were not established. Objectives: To evaluate the EBV serological profile in pSS patients, considering the current glucocorticoid and immunosuppressive treatments, organic affections and the disease activity score. Methods: We evaluated 100 pSS patients (American-European Criteria) and 89 age/gender/ethnicity-matched healthy controls. Disease activity was measured by EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI). Serum antibodies to EBV (anti-VCA IgG/IgM, anti-EBNA-1 IgG and anti-EA-D IgG) were determined by ELISA. Results: Patients and controls had comparable frequencies and mean levels of anti-VCA IgG (90 vs. 86.5%, p=0.501; 2.6±1.1 vs. 2.5±1.1 AU/mL, p=0.737) and anti-EBNA-1 IgG (92 vs. 94.4%, p=0.576; 141.3 ±69.8 vs. 135.6±67.5 RU/mL, p=0.464), with anti-VCA IgM uniformly negative. Noteworthy, higher frequency and increased mean levels of anti-EA-D occurred in patients than controls (36 vs. 4.5%, p<0.0001; 38.6±57.4 vs. 7.9±26.3 RU/mL, p<0.0001). Frequency of anti-EA-D positive (28.6 vs. 4.5%, p=0.0001) and mean levels of this reactivity (30.2±51.5 vs. 7.9±26.3 RU/mL, p=0.0002) were also higher in pSS patients without any glucocorticoid and/or immunosuppressive therapy (n=49) than in healthy controls (n=89), in spite of comparable age (p=0.628), gender (p=1.000) and ethnicity (p=1.000). Further analysis of pSS patients with (n=36) and without (n=64) anti-EA-D revealed comparable age (47.8±11.0 vs. 47.6±10.8 years, p=0.925), gender (female: 100 vs. 95.3%, p=0.551), ethnical distribution (white: 66.7 vs. 67.2%, p=1.000), disease duration (8.9±5.4 vs. 8.3±5.0 years, p=0.578), current prednisone dose (4.8±6.9 vs. 5.1±10.4 mg/day, p=0.319), current uses of prednisone (52.8 vs. 37.5%, p=0.148) and immunosuppressants (44.4 vs. 31.3%, p=0.201). ESSDAI-values were comparable (p=0.102), but joint activity (ESSDAI criteria) was more frequent (25 vs. 9.4%, p=0.045) in anti-EA-D positive patients. Anti-EA-D was not associated with anti-Ro-SSA (p=1.000), anti-La-SSB (p=0.652), rheumatoid factor (p=1.000), anti-alpha-fodrin (p=0.390) or antiphospholipid antibodies (p=0.573), not suggesting cross-reactivity. Conclusions: The finding of elevated serum levels of anti-EA-D antibody even in the absence of glucocorticoid or immunosuppressive treatment suggests the involvement of EBV in the pathogenesis of pSS. In addition, the new association of anti-EA-D with joint activity raises the possibility that a subclinical EBV reactivation may trigger or perpetuate the articular involvement in pSS. Disclosure of Interest: S. Pasoto Grant/Research support from: Agency for Promotion of Research (FAPESP), R. Natalino Grant/Research support from: Agency for Promotion of Research (FAPESP), H. Chakkour Grant/Research support from: Agency for Promotion of Research (FAPESP), V. Viana: None Declared, C. Bueno: None Declared, E. Leon: None Declared, M. Vendramini: None Declared, M. Levy Neto: None Declared, E. Bonfa: None Declared